A Secure Data Collection Method Based on Deep Reinforcement Learning and Lightweight Authentication - Yunlong Wang; Jie Zhang; Guangjie Han; Dugui Chen (World Electric Vehicle Journal)
Cooperative Unmanned Aerial Vehicle (UAV) technology can significantly improve data acquisition in Internet of Things (IoT) environments, which are characterized by wide distribution and limited capacity of ground-based devices. However, due to the open nature of wireless communications, such applications face security threats posed by UAV authentication, especially in scalable IoT environments. To address such challenges, we propose a lightweight chain authentication protocol for scalable IoT environments (LCAP-SIoT), which uses Physical Unclonable Functions (PUFs) and distributed authentication to secure communications, and a secure data collection algorithm, named LS-QMIX, which fuses the LCAP-SIoT and Q-learning Mixer (QMIX) algorithm to optimize the path planning and cooperation efficiency of the multi-UAV system. According to simulation analysis, LCAP-SIoT outperforms existing solutions in terms of computing and communication costs, and LS-QMIX results in superior performance in terms of data collection rate, task completion time, and the success rate of authentication for newly joined UAVs, indicating the feasibility of LS-QMIX in dynamic expansion scenarios.